Prioritizing Key Stunting Risk Factors Using a Fuzzy DEMATEL-Based Group Decision Making Approach - Taufiq Dwi Cahyono; Wiwien Hadikurniawati (Universitas Stikubank, 2026)
The Multi-Criteria Group Decision Making (MCGDM) approach uses the fuzzy DEMATEL method to assess the criteria for stunting in toddlers. This involves data with numerical values, being fuzzy numbers, numbers that represent subjective judgments by eight decision makers. The study aims to identify and prioritize the critical factors that contribute to stunting in children, which can help policymakers to develop effective interventions to reduce stunting rates. The approach combines fuzzy set theory and the DEMATEL method to handle the uncertainty and vagueness of the decision-making process. The results show that the proposed approach can effectively identify and prioritize the critical factors that contribute to stunting, which can help policymakers to develop targeted interventions to reduce stunting rates. The study contributes to the field of multi-criteria decision-making by providing a novel approach that can handle the uncertainty and vagueness of the decision-making process in evaluating complex problems such as stunting. The MCGDM results are based on four criteria and the ranking is determined using the fuzzy DEMATEL. The analysis and calculations show that the main criteria based on the highest value obtained is mother nutrition.